Balance of Payments Statistics Yearbook 2013. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2013)
Composed of international economic transactions data, BOPS delivers critical statistical information that covers: total goods, services, income, and current transfers an economy receives from or provides to the rest of the world; capital transfers and changes in each economy's external financial claims and liabilities; tables featuring area and world totals of balance of payments; and IIP components and aggregates. The IMF Balance of Payments Statistics contains over 200,000 quarterly and annual time series data. The data include aggregate as well as detailed information in the form of analytical and standard component presentations for countries. Additional documentation is included with descriptions of methodologies, compilation practices, and data sources used by individual member countries in compiling their balance of payments and international investment position statistics.